Toxidez por cobre e zinco na germinação de sementes e no desenvolvimento de trigo mourisco - Bastiani, Géssica Gaboardi de (2020)
Abstract - In the grapevines culture due to the favorable climate for fungal diseases foliar is indispensable successive applications of fungicides. The most used is the Bordeaux mixture, consisting mainly of copper (Cu) that said there was an increase significant in the content of this element in the soil, reaching toxic levels for plants. Thus, recently, alternatives for replacing this product have been sought, in order to decrease the amount of Cu in these grapevines. One alternative found was substitution by fungicides consisting of zinc (Zn). The increase in these elements available in the soil can impair the development of both the vine and the cover plants. Buckwheat (Fagopyrum esculentum Moench) is a great option for ground cover due to the high dry mass production, low cost and high degree of rusticity. Thus, the objective of this study was to evaluate the effect of excess Cu and Zn isolates on germination, growth and development of buckwheat. For this, two studies were carried out and physiological and biochemical variables were analyzed in buckwheat seedlings and plants. The treatments were composed of two cultivars IPR 92 Altar and IPR 91 Baili, each cultivar was subjected to different Cu and Zn treatments. Study I was divided into two experiments, where in experiment I the concentrations of Cu used were 0, 5, 10, 15 and 20 mg L-1 (in the form of CuSO4) and in experiment II Zn was applied in the concentrations 0, 8, 16, 24 and 32 mg L-1 of ZnSO4 (60%) and ZnCl2 (40%). Were evaluated physiological and biochemical variables linked to oxidative stress in seedlings, and the cytotoxic effect. For study II, which was also divided into two experiments, buckwheat plants were grown until full bloom, conducted in vessels, where for experiment I the concentrations of Cu used were 0, 2, 4 and 6 mg L-1 (in the form of CuSO4) and experiment II used Zn concentrations in doses of 0, 3, 6, 9 and 12 mg L-1 of ZnSO4 (60%) and ZnCl2 (40%). Were evaluated physiological, nutritional and biochemical variables linked to oxidative stress. At the study I the concentrations of Cu and Zn used were not significant to cause damage to the germinative process, however they caused moderate toxicity to the plants of buckwheat evidenced by the decrease in growth variables. O antioxidant defense system of buckwheat plants has been activated and effective enough to reverse the stress condition, especially in seedlings submitted to Zn doses. From this study, it was possible to conclude that buckwheat presents potential in the initial establishment, being adequate when used as cover plant in an environment with excess Cu and Zn. In study II, concentrations of Cu and Zn used caused toxicity in concentrations extreme conditions, evidenced by the decrease in plant growth. The system of antioxidant defense of buckwheat plants has been activated and effective to reverse the stress condition. Concentrations of up to 2 mg L-1 of Cu and 6 mg L-1 of Zn caused damage to the plant development of cultivars IPR 91 Baili and IPR 92 Altar of Buckwheat, which can show its potential when used as a plant cover when grown in an environment with excess Cu and Zn.